Effect of varieties and pinching days on growth and yield attributes of African marigold (Tagetes erecta L.) - Bhusal, Karishma; Bhusal, Pooja; Acharya, Nirajan; Chapai, Dharma Prasad; Shrestha, Jiban (Nepal Agriculture Research Journal, 2023)
From June to August 2021, a field experiment was carried out at the College of Natural Resource Management, Puranchaur-19, Kaski to examine the effects of pinching on the vegetative growth and yield characteristics of African marigold (Tagetes erecta L.). Two major varieties, Karma-666 and Karma-555, were evaluated in the experiment with three different dates of pinching (Control, 20 DAT, and 40 DAT), which were set up in a Randomized Complete Block Design (RCBD) with four replications. According to the findings, at 5% level of significance, no significant difference was found in the interaction effect between growth and floral characters. Karma-555 showed greater plant spread (34.77 cm) and more branches per plant (13.73) than Karma-666. Additionally, Karma-555 was found to have a higher number of flowers plant-1 (39.10) and flower yield plant-1 (335.77 g). However, Karma-666 had significantly (P <0.001) high fresh flower weight (10.51 g) and flower diameter (7.18 cm). Plants pinched at 20DAT were found to be the most effective for enhancing vegetative growth parameters and flower yield.